The crisis of imprisonment: protest, politics, and the making of the American penal state, 1776-1941 - McLennan, Rebecca M. (Cambridge historical studies in American law and society, 2008)
Introduction: The grounds of legal punishment -- Strains of servitude : legal punishment in the early republic -- Due convictions : contractual penal servitude and its discontents -- Commerce upon the throne : the business of imprisonment in Gilded Age America -- Disciplining the state, civilizing the market : the abolition of contract prison labor -- A model servitude : prison reform in the early Progressive Era -- Uses of the state : dialectics of reform in early progressive New York -- American bastille : Sing Sing and the political crisis of imprisonment -- Changing the subject : the metamorphosis of prison reform in the high Progressive Era -- Laboratory of social justice : the new penologists at Sing Sing -- Punishment without labor : towards the modern penal state -- Conclusion: On the crises of imprisonment